2007
DOI: 10.1289/ehp.9366
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Di( n -butyl) Phthalate and Testicular Dysgenesis: Comparison of Fetal and Adult End Points and Their Dose Sensitivity

Abstract: BackgroundFetal exposure of male rats to di(n-butyl) phthalate (DBP) induces reproductive disorders similar to those in human testicular dysgenesis syndrome (TDS), including infertility, cryptorchidism, focal “dysgenetic areas,” and Sertoli cell–only tubules in the adult testis. Humans are widely exposed to DBP, but at much lower levels than those causing adverse effects in rats.ObjectivesThe objective of this study was to evaluate end points affected by DBP action in rats in fetal and adult life that are rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 49 publications
7
88
0
Order By: Relevance
“…Interestingly, we observed that BPAF induced a dose-dependent increase of multinucleated cells. Induction of abnormal testicular germ cells, such as multinucleated germ cells (MNGs), has been reported following gestational exposure to di-(n-butyl) phthalate (DBP) (Fisher et al, 2003;Kleymenova et al, 2005;Mahood et al, 2007;Saffarini et al, 2012). Ferrara and colleagues speculated that germ cells presenting DBP-induced MNGs may develop into carcinoma in situ cells, the known precursors of testicular germ cell tumors in men (Ferrara et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed that BPAF induced a dose-dependent increase of multinucleated cells. Induction of abnormal testicular germ cells, such as multinucleated germ cells (MNGs), has been reported following gestational exposure to di-(n-butyl) phthalate (DBP) (Fisher et al, 2003;Kleymenova et al, 2005;Mahood et al, 2007;Saffarini et al, 2012). Ferrara and colleagues speculated that germ cells presenting DBP-induced MNGs may develop into carcinoma in situ cells, the known precursors of testicular germ cell tumors in men (Ferrara et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of dysgenetic tubules in testis in exposed groups is a finding that is commonly seen with exposure to certain phthalates including DEHP and DBP (Jarfelt et al 2005, Mahood et al 2007, and these effects are assumed to be related to the phthalate content of the mixture, but are not directly related to the sperm count reduction.…”
Section: Reproductive Aging In Malesmentioning
confidence: 99%
“…In mammals, including humans, phthalate exposure is associated with endocrine disruption [15][16][17] and metabolic disorders [18,19]. In rodents, in utero exposure to phthalates results in developmental and reproductive defects similar to those termed testicular dysgenesis syndrome in humans [20][21][22].…”
Section: Introductionmentioning
confidence: 99%